Duration of Dual Antiplatelet Therapy After Implantation of Drug-Coated Balloon - Zhang, Yuxuan; Zhang, Xinyi; Dong, Qichao; Chen, Delong; Xu, Yi; Jiang, Jun (Frontiers in Cardiovascular Medicine, 2021)
The drug-coated balloon (DCB) is an emerging percutaneous coronary intervention (PCI) device with theoretical advantages and promising results. Recent clinical observations have demonstrated that DCB tends to have both good efficacy and a good safety profile in the treatment of in-stent restenosis (ISR) for both bare-metal and drug-eluting stents (DES), de novo coronary artery disease (CAD), and other situation, such as high bleeding risk, chronic total occlusion, and acute coronary syndrome (ACS). Dual antiplatelet therapy (DAPT) has become an essential medication in daily clinical practice, but the optimal duration of DAPT after the implantation of a DCB remains unknown. At the time of the first in vivo implantation of paclitaxel-DCB for the treatment of ISR in 2006, the protocol-defined DAPT duration was only 1 month. Subsequently, DAPT duration ranging from 1 to 12 months has been recommended by various trials. However, there have been no randomized controlled trials (RCTs) on the optimal duration of DAPT after DCB angioplasty. Current clinical guidelines normally recommend the duration of DAPT after DCB-only angioplasty based on data from RCTs on the optimal duration of DAPT after stenting. In this review, we summarized current clinical trials on DCB-only angioplasty for different types of CADs and their stipulated durations of DAPT, and compared their clinical results such as restenosis, target lesion revascularization (TLR) and stent thrombosis event. We hope this review can assist clinicians in making reasonable decisions about the duration of DAPT after DCB implantation.